2010
DOI: 10.1051/0004-6361/200912356
|View full text |Cite
|
Sign up to set email alerts
|

Mn, Cu, and Zn abundances in barium stars and their correlations with neutron capture elements

Abstract: Barium stars are optimal sites for studying the correlations between the neutron-capture elements and other species that may be depleted or enhanced, because they act as neutron seeds or poisons during the operation of the s-process. These data are necessary to help constrain the modeling of the neutron-capture paths and explain the s-process abundance curve of the solar system. Chemical abundances for a large number of barium stars with different degrees of s-process excesses, masses, metallicities, and evolu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 66 publications
(105 reference statements)
3
17
1
Order By: Relevance
“…This may indicate that Mn and Cu do not share the same nucleosynthetic origin. Indeed, Allen & Porto de Mello (2011) found that the synthesis of Cu receives a larger contribution from not so massive stars than Zn, a result roughly in line with those of Castro et al (1999) and ours. Such results point towards the necessity of both more extensive observations of the abundances of Cu and Zn, and more protracted theoretical efforts, in order that a better understanding of the complex chemical history of these two elements may be achieved.…”
Section: Abundance Trends As a Function Of [Ba/fe]supporting
confidence: 93%
See 3 more Smart Citations
“…This may indicate that Mn and Cu do not share the same nucleosynthetic origin. Indeed, Allen & Porto de Mello (2011) found that the synthesis of Cu receives a larger contribution from not so massive stars than Zn, a result roughly in line with those of Castro et al (1999) and ours. Such results point towards the necessity of both more extensive observations of the abundances of Cu and Zn, and more protracted theoretical efforts, in order that a better understanding of the complex chemical history of these two elements may be achieved.…”
Section: Abundance Trends As a Function Of [Ba/fe]supporting
confidence: 93%
“…A decreasing trend in [Zn/Fe] vs. [Fe/H] is seen for stars poorer than the Sun, in agreement with Fig. 1 of Allen & Porto de Mello (2011).…”
Section: Abundance Trends As a Function Of [Fe/h]supporting
confidence: 88%
See 2 more Smart Citations
“…However, we do not find such a tight correlation with any of the other heavy-s or light-s elements. Later, the work by Allen & Porto de Mello (2011) did not find that Cu-Ba correlation in a sample of barium and normal stars while Zn showed increasing trends with Ba, Sr, Y, Nd, and more tight increasing trends with Eu, and other r-elements (Gd and Dy). Those authors conclude that the r-process is contributing to Zn production with a higher proportion than to Cu for those stars.…”
Section: Relative Contribution Of R-and S-process Elements Along the mentioning
confidence: 93%